Revisiting Ecological Precarity in Southeastern Nigeria and the Igbo Poets’ Response - Aguobi, Nkechinyere Faith; Ikwubuzo, Iwu Remigius Obi (NIU Journal of Humanities, 2026)
This paper examines the intersection of ecological degradation and poetic response in Southeastern Nigeria, focusing on how Igbo poets engage environmental crises through literary imagination and advocacy. Drawing on Reed’s culturally grounded ecocritical model, the study explores how selected poems articulate ecological precarity and construct an indigenous ethic of environmental sustainability. Four poems were purposively selected and subjected to close textual analysis to assess their ecological orientation and symbolic structure. The analysis demonstrates that Igbo poets move beyond aesthetic celebration of nature to critically interrogate its degradation, transforming poetry into a site of environmental consciousness and ethical reflection. Environmental decline is represented simultaneously as material devastation and moral rupture: gully erosion is metaphorically rendered as a corporeal wound upon the land; polluted rivers signify spiritual desecration; and biodiversity loss is attributed not only to ecological pressures but also to culturally mediated neglect shaped by aesthetic bias and symbolic prejudice. Through nuanced poetic devices, Igbo poets recast environmental concerns as a disruption of reciprocity between humans and the natural world. Sustainability is therefore framed not as a purely technocratic intervention but as a moral imperative grounded in indigenous cosmology. The study concludes that Igbo ecopoetry constitutes a significant indigenous contribution to environmental thought, advancing a model of sustainability rooted in relational balance, communal accountability, and ethical renewal. Igbo poets thus emerge not only as chroniclers of environmental crisis but as critical agents in shaping an environmentally conscious cultural imagination. Keywords: Ecological degradation, Environmental realities, Igbo poets, Sustainability, Southeastern Nigeria.